Information technologies in English teaching - Mirochnik, Vira (My University, 2014)
The article is concerned about using a variety of computer technology and Internet resources for successful English learning.
Keywords: teaching a foreign language; викладання іноземної мови; інтернет навчання; online learning; кафедра ділової іноземної мови та міжнародної комунікації